Observation of the annihilation decay mode B0→K+K− - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physical review letters, 2017)
A search for the B0→K+K− decay is performed using pp-collision data collected by LHCb. The data set corresponds to integrated luminosities of 1.0 and 2.0 fb−1 at center-of-mass energies of 7 and 8 TeV, respectively. This decay is observed for the first time, with a significance of more than 5 standard deviations. The analysis also results in an improved measurement of the branching fraction for the B0s→π+π− decay. The measured branching fractions are B(B0→K+K−)=(7.80±1.27±0.81±0.21)×10−8 and B(B0s→π+π−)=(6.91±0.54±0.63±0.19±0.40)×10−7. The first uncertainty is statistical, the second is systematic, the third is due to the uncertainty on the B0→K+π− branching fraction used as a normalization. For the B0s mode, the fourth accounts for the uncertainty on the ratio of the probabilities for b quarks to hadronize into B0s and B0 mesons.
R. Aaij, P. d’Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D.Gerick, E. Gersabeck, X.Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, P. Seyfert, M. Schiller, M. Stahl, S. Stemmle, J. v. Tilburg, U. Uwer, M. Vesterinen, R. Waldi, A. Zhelezov [und weitere]
Im Titel sind die Zeichen "0" , "+" und "-" hochgestellt
Gesehen am 30.10.2018